The biology and evolution of spider venoms. (28th August 2021) - Lüddecke, Tim; Herzig, Volker; von Reumont, Björn M.; Vilcinskas, Andreas
ABSTRACT: Spiders are diverse, predatory arthropods that have inhabited Earth for around 400 million years. They are well known for their complex venom systems that are used to overpower their prey. Spider venoms contain many proteins and peptides with highly specific and potent activities suitable for biomedical or agrochemical applications, but the key role of venoms as an evolutionary innovation is often overlooked, even though this has enabled spiders to emerge as one of the most successful animal lineages. In this review, we discuss these neglected biological aspects of spider venoms. We focus on the morphology of spider venom systems, their major components, biochemical and chemical plasticity, as well as ecological and evolutionary trends. We argue that the effectiveness of spider venoms is due to their unprecedented complexity, with diverse components working synergistically to increase the overall potency. The analysis of spider venoms is difficult to standardize because they are dynamic systems, fine‐tuned and modified by factors such as sex, life‐history stage and biological role. Finally, we summarize the mechanisms that drive spider venom evolution and highlight the need for genome‐based studies to reconstruct the evolutionary history and physiological networks of spider venom compounds with more certainty.